MASTERING OF FLAT BAND PRODUCTION FOR HIGH-LOADED HYDRAULIC HOSES - A. V. Vedeneev; O. I. Ignatenko (Литьë и металлургия)
The different methods at determination of tensile strength and cross-sectional area of flat wire are analyzed. Such technological parameters as drawing-out and widening at upset spreading are examined.